2015
DOI: 10.3920/qas2014.0509
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical composition of some oils extracted from seeds roasted at different temperatures

Abstract: Oil seeds are commonly used in cooking, frying and as salad oil and have commercial and economic importance. Since the seeds are roasted before pressing of the oil, changes occur in their composition; thus it is crucial to modify roasting process to minimise adverse effects. This study reflects the effects of different roasting temperatures (90, 150 and 210 °C for 10 min. in conventional oven) on the oil constituents and some chemical properties of oils from the seeds of sesame, sunflower, soybean, flaxseed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The studies on the effects of roasting on the chemical composition and the oxidative stability of argan oil are not numerous. In addition, the temperature used by the authors remains relatively low (110°C) [ 11 , 36 , 37 ] compared to works done on other oilseeds [ 6 , 7 , 29 , 38 ], but also with regard to the temperatures applied for the traditional extraction of argan oil intended for commerce or for a familiar use. Indeed, the extraction of argan oil is mainly done using the artisanal process, especially in rural areas of southern Morocco.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on the effects of roasting on the chemical composition and the oxidative stability of argan oil are not numerous. In addition, the temperature used by the authors remains relatively low (110°C) [ 11 , 36 , 37 ] compared to works done on other oilseeds [ 6 , 7 , 29 , 38 ], but also with regard to the temperatures applied for the traditional extraction of argan oil intended for commerce or for a familiar use. Indeed, the extraction of argan oil is mainly done using the artisanal process, especially in rural areas of southern Morocco.…”
Section: Resultsmentioning
confidence: 99%
“…As regards the effect of roasting on the content of tocopherols which represent the major antioxidants of vegetable oils, the data from the literature are inconsistent. Depending on the nature and variety of oilseeds, roasting may lead to a decrease [ 5 – 7 ] or an increase in tocopherols level in oil [ 8 10 ]. Since tocopherols are thermosensitive, their final concentration in the oil will depend essentially on the temperature and the duration of the roasting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the obtained results showed that the rate of polyunsaturated fatty acid oxidation was less in the oil extracted from the flaxseeds with leaves, particularly blanched leaves, at a level of 5%–7.5% compared with the control sample (Table 3 ). It has been reported that flaxseed oil is sensitive to oxidation, and its 18:3 and 18:2 content has been decreased during processing and the storage (Simsek et al., 2015 ). The obtained results in this study agree with the previously published data (Jung et al., 2021 ; Mikołajczak & Tańska, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Different pre-treatments such as moisture adjustment, roasting, ohmic heating and microwaving can be used to enhance the oil extraction yield and also to improve the extracted oil quality [10][11][12][13]. It is also possible to change the temperature during oil extraction from nuts and oilseeds by pressing and to use higher temperatures up to 200 • C [14].…”
Section: Introductionmentioning
confidence: 99%